Optimization of alkali fusion process for determination of I-129 in solidified radwastes by neutron activation. (October 2021) - Chao, Jiunn-Hsing; Chuang, Chun-Yu; Chou, Wei-Chun; Kuo, Chun-Liang; Chang, Feng-Chih; Chiang, An-Chung
Abstract: This study determines the optimum temperature for the alkali fusion process used to effectively separate iodine from solidified radwaste attaining low-level 129 I by neutron activation. The alkali fusion temperature was adjusted to 120, 200, and 400 °C to approach the optimum conditions associated with a good statistical distribution of the measured 129 I data and high chemical recovery yield. Statistical analysis revealed that the optimum temperature of the alkali fusion process was 200 °C, displaying good central tendency and low variance of the measured 129 I data, and the respective chemical recovery yields were higher than other temperatures. The optimum fusion condition provides more reliable scaling factors ( 129 I/ 137 Cs) of radwaste. Highlights: Alkali fusion technique for determination of 129 I was studied. The optimum fusion process was associated with good statistical distribution of 129 I data. The optimum fusion temperature was determined to be 200 °C. The yield (64%) in the optimum fusion process was higher than other temperatures.